(untitled) (Revista de História Regional, 2007)
The text points to the origins of the Brazilian agrarian subject, characterized by the social, economic and historical latifundium system prevalence, determining the subjection of most of the population, basically constituted of workers without earth and small rural producers, to the interest and needs of the great production, generally orientated to the external market. The production and dominance relationship generated at the colonial time and largely preserved in the rural zone, are not only of economic, but social and ideological order, constituting obstacles for most of the rural population to get conscious of its possibilities of getting free from a situation of poverty and oppression.